A Novel Current-Mode SIMO Type Universal Filter Using CFTAs - Herencsár, Norbert; Koton, Jaroslav; Vrba, Kamil; Mišurec, Jiří (Hikari Ltd., 2009)
In this paper a new active element for the realization of current-mode analog blocks Current Follower Transconductance Amplifier (CFTA) is presented. The element is a combination of the Current Follower (CF) and the Balanced Output Transconductance Amplifier (BOTA). In the paper we also document another extended active element CFTA which has more current outputs than can be realized by the UCC-N1B circuit, which was developed at our workplace. The application of this active element is shown on the realization of current-mode second-order universal frequency filters of the type SIMO (single-input- multi-output). The circuit structure consists of three active and three passive elements. The circuit was analyzed using signal-flow graphs. The properties of the proposed universal filter were subjected to a sensitivity analysis and AC analysis using PSpice software.

In this paper a new active element for the realization of current-mode analog blocks Current Follower Transconductance Amplifier (CFTA) is presented. The element is a combination of the Current Follower (CF) and the Balanced Output Transconductance Amplifier (BOTA). In the paper we also document another extended active element CFTA which has more current outputs than can be realized by the UCC-N1B circuit, which was developed at our workplace. The application of this active element is shown on the realization of current-mode second-order universal frequency filters of the type SIMO (single-input- multi-output). The circuit structure consists of three active and three passive elements. The circuit was analyzed using signal-flow graphs. The properties of the proposed universal filter were subjected to a sensitivity analysis and AC analysis using PSpice software.
A Novel Current-Mode SIMO Type Universal Filter Using CFTAs
Keywords: Current Follower Transconductance Amplifier (CFTA); current-mode circuit; universal filter; signal-flow graph; Universal Current Conveyor (UCC); BOTA; Current Follower Transconductance Amplifier (CFTA); current-mode circuit; universal filter; signal-flow graph; Universal Current Conveyor (UCC); BOTA